Influence of Low-Level Laser Irradiation of the Red and Infrared Spectral Range for Treating Chronic Testicular Pain: A Randomized Clinical Trial: Low-level laser irradiation for treating chronic testicular pain - Momenzadeh, Cyrus; Dehghani-Ghorbi, Mahmoud; Razzaghi, Mohammad Reza; Abbasi, Mohammad Zaki; Jaffari, Alireza (Journal of Lasers in Medical Sciences, 2024)
Introduction: The treatment of chronic testicular pain is a complex condition that will be encountered by most practicing clinicians. In this study, the influence of low-level laser irradiation of the red and infrared spectral range for treating chronic testicular pain was evaluated and compared. Methods: In this double-blind, placebo-controlled randomized clinical trial study, 60 patients were randomly divided into three groups of 20: (1) low-level laser group with red (650 nm, 50 mW), (2) low-level laser group with infrared (820 nm, 100 mW) and (3) laser placebo group. The treatment protocol consisted of 15 minutes, three times a week, for only 12 sessions. Then the patients were evaluated for pain and sexual satisfaction during the follow-up. Results: There was a significant reduction in the pain score in the two groups of the low-level laser group with red (650 nm, 50 mW) and the low-level laser group with Infrared (820 nm, 100 mW) spectra compared with the control, at 6 and 12 weeks after the treatment (P<0.05). Also, the level of sexual satisfaction in the two groups of low-power laser with red and infrared spectra showed a significant improvement (P<0.05). Conclusion: Low-level laser therapy is a safe, non-invasive, and useful method for treating patients with chronic testicular pain. Therefore, red (650 nm, 50 mW) and Infrared (820 nm, 100 mW) spectra low-level laser therapies improve testicular pain and sexual satisfaction.